1989
DOI: 10.1016/s0010-9452(89)80024-3
|View full text |Cite
|
Sign up to set email alerts
|

Space Exploration with and without the Aid of Vision in Hemisphere-Damaged Patients

Abstract: Space exploration carried out under visual control and in its absence (blindfolded condition) was investigated in 20 RBD patients, 10 LBD patients and 20 normal controls with a modified version of Chedru's test (pressing the keys of a keyboard). Conventional tests for visual hemi-inattention permitted to classify RBD patients in a group with visual neglect (RBD VN+) and a group without visual neglect (RBD VN-). On the visual version of the test both RBD groups showed a preference for pressing the keys ipsilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 10 publications
2
13
0
1
Order By: Relevance
“…= 0.32; t (11) = 0.04; P > 0.96; see Table 4). This finding is consistent both with previous results [23,26,31,34,49,66] and with the "pseudoneglect" phenomenon originally described by Bowers and Heilman [8]. The length of the line did not significantly affect the position of the subjective middle (see Table 4).…”
Section: Control Subjectssupporting
confidence: 92%
See 4 more Smart Citations
“…= 0.32; t (11) = 0.04; P > 0.96; see Table 4). This finding is consistent both with previous results [23,26,31,34,49,66] and with the "pseudoneglect" phenomenon originally described by Bowers and Heilman [8]. The length of the line did not significantly affect the position of the subjective middle (see Table 4).…”
Section: Control Subjectssupporting
confidence: 92%
“…According to Gentilini and coworkers [26], the increase in ipsilateral responses when key pressing was guided by vision in comparison to the blindfolded condition suggests that incoming sensory stimuli from the ipsilateral side play a role in shifting attention towards it and in enhancing neglect of controlateral space. In fact, although several experiments have shown that attention can be allocated to different parts of the spatial field without overt eye movements (for review see [51]), experiments performed in normals have suggested that eye movements cannot be made without shifting the focus of attention in the same direction (for review see [24]).…”
Section: Absence Of Significant Spatial Bias In Normal and Neglect Pamentioning
confidence: 99%
See 3 more Smart Citations